RISKS MANAGEMENT OF FOREIGN ECONOMIC ACTIVITIES ENTERPRISES IN THE CONDITIONS OF WAR - Савків, Уляна Степанівна; Сидор, Галина Вікторівна; Тимків, Андрій Олександрович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
In the conditions of war, the problem of enterprise risk management becomes more acute. Risk management systems used by business entities in peacetime turned out to be ineffective in wartime. They are unable to prevent significant economic losses in the course of companies’ foreign economic activity. Solving these tasks can be considered through the lens of analyzing the company’s risk management algorithm. The goal is to develop a mechanism and an effective system for managing foreign economic risks in wartime conditions. To achieve the goal, general and special research methods were used in this article, particularly: general scientific and special research methods – to ensure the achievement of the goal and abstract-logical and dialectical methods of analysis – to substantiate theoretical positions and conclusions. The relevance of the material is presented in the article due to the fact that traditional approaches to risk management must be reviewed and improved. The war caused problems for participants in foreign economic activity. Importers and exporters cannot fulfill their obligations on time or in full, so it is necessary to implement an effective mechanism for managing the risks of foreign economic activity into the management system. A risk management algorithm has been developed. The following sequence of actions is proposed: risk identification; risk identification; assessment of the degree of risk impact on the enterprise; definition of risk management methods and tools; eliminating the risk or reducing the level of its impact; monitoring and control. This will allow solving the problems that arise in the changing external and internal environments, simplifying the decision-making procedure regarding risks, and reducing the costs of their management. It was established that risks have a double impact on foreign economic activity. On the one hand, they create barriers in functioning, on the other hand, they stimulate the search for new solutions and ideas. Changes in the risk management system are proposed, which will ensure a higher level of competitiveness of the enterprise. An improved system of risk management in the foreign economic activity of the enterprise will contribute to the reduction of losses.